MANIPULATIF FISIK DALAM PENGENALAN BENTUK ALJABAR - Tundung Memolo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Incorporating manipulatives into math lessons in a meaningful way, helping students understand concepts more easily, and make teaching more effective. But in the field are still found many students who have not mastered the basic concept of algebraic form. Because of the importance of the use of physical manipulative in the learning of mathematics, in this study is limited in learning the form of algebra for class VII using the 2013 curriculum. The purpose of this paper is how to introduce algebraic form using physical manipulative as well as to know how much students' ability to understand the concept of variables, constants, coefficients, and write them in algebraic form. This research method is including best practice research.The subject of this research is the students of class VII B with the method of collecting data in the form of documentation in the form of written test and photo activity. Data were analyzed descriptively. The use of physical manipulative can be used in introducing algebraic form; the teacher introduces the concept of variables, coefficients, and constants such as using a bullet place, a bullet and a bullet. The result of the students' understanding about the variables, coefficients, constants, and writing algebraic forms is that 33% of students are categorized very well and 48% of students are categorized well. Keywords: aljabar, fisik, konsep, manipulatif, variabel